The Impact of Perceived Greenwashing on Customer Satisfaction and the Contingent Role of Capability Reputation - Ioannou, Ioannis; Kassinis, George; Papagiannakis, Giorgos (Journal of business ethics, 2023)
We investigate the impact of perceived greenwashing on customer satisfaction. Unlike prior research that largely examines customer perceptions associated with irresponsible behavior, we focus on cases where firms overcommit and/or do not deliver on promised socially responsible actions. We theorize that this type of greenwashing is associated with lower customer satisfaction because customers perceive greenwashing through the lens of corporate hypocrisy. Using data from the American Customer Satisfaction Index (ACSI) for U.S. companies during the period 2008–2016, we document a negative link between perceived greenwashing related to green product innovation (GPI) and the ACSI index. We demonstrate that this effect is primarily triggered by corporate policies exceeding the corresponding implementation actions and not by lower levels of implementation. We also show that a firm’s capability reputation mitigates the negative effect of greenwashing on customer satisfaction. Moreover, we conduct an experiment and provide evidence confirming that GPI greenwashing is in fact perceived by customers as corporate hypocrisy.